1989
DOI: 10.1111/j.1432-1033.1989.tb14643.x
|View full text |Cite
|
Sign up to set email alerts
|

Trypanothione reductase from Trypanosoma cruzi

Abstract: Trypanothione reductase of Trypanosoma cruzi is a key enzyme in the antioxidant metabolism of the parasite. Here we report on the enzymic and pharmacological properties of trypanothione reductase using glutathionylspermidine disulfide as a substrate.1. Both pH optimum (7.5) and the ionic strength optimum (at 30 mM) are unusually narrow for this enzyme. 40 mM Hepes, 1 mM EDTA, pH 7.5 was chosen as a standard assay buffer because in this system the k,,,/K, ratio had the highest values for both natural substrates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
93
0
5

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(103 citation statements)
references
References 25 publications
3
93
0
5
Order By: Relevance
“…For example, NADH might promote oxidative phosphorylation, generating the proton-driven force in the form of an electrochemical potential that can drive the synthesis of ATP (101). Moreover, NADPH serves as a cofactor for trypanothione reductase (102). Indeed, we have observed that P5C can serve as a viable energy source in the ATP production, which was supported by our data showing that antimycin A inhibits this process.…”
Section: Discussionsupporting
confidence: 76%
“…For example, NADH might promote oxidative phosphorylation, generating the proton-driven force in the form of an electrochemical potential that can drive the synthesis of ATP (101). Moreover, NADPH serves as a cofactor for trypanothione reductase (102). Indeed, we have observed that P5C can serve as a viable energy source in the ATP production, which was supported by our data showing that antimycin A inhibits this process.…”
Section: Discussionsupporting
confidence: 76%
“…The literature showed that the inhibition of the trypanothione reductase was a possible mechanism of action of nitrofurazone (22,23,24); Trossini and coworkers (16) showed cruzipain inhibition and an increase of 30% in affinity for the enzyme. In addition, the most interesting and important point is the simplicity of the NFOH synthesis and its high yield (10), suggesting a very cheap compound for chemical scale-up.…”
Section: Discussionmentioning
confidence: 99%
“…After the initial work of Henderson and co-workers (1988) naphthoquinone derivatives were further investigated for their action on TR (Jockers-Scherubl et al 1989, Salmon-Chemin et al 2000. In a previous work we reported the in vitro effect of several naphthothiophenquinone derivatives against epimastigote and trypomastigote forms of T. cruzi and the inhibition of the recombinant enzyme trypanothione reductase (Zani et al 1997).…”
Section: Its Mode Of Inhibition Fits a Non-competitive Model With Resmentioning
confidence: 99%
“…Using either rational or empiric approaches, different classes of compounds, including peptides and peptoid, substituted polyamines, quinacrine and acridine analogues, 2-aminodiphenylsulfides, phenothiazine derivatives, substituted piperazines and nitrofuran derivatives, were studied for their inhibitory potential (see reviews by Werbovetz 2000, Augustyns et al 2001, Schmidt & KrauthSiegel 2002. Investigation of natural products, although not so extensive, disclosed interesting inhibitors such as ajoene from garlic (Gallwitz et al 1999), bisbenzylisoquinoline alkaloids (Fournet et al 1998(Fournet et al , 2000, and polyamines such as lunarine (Bond et al 1999) and kukoamine (Ponasik et al 1995).After the initial work of Henderson and co-workers (1988) naphthoquinone derivatives were further investigated for their action on TR (Jockers-Scherubl et al 1989, Salmon-Chemin et al 2000. In a previous work we reported the in vitro effect of several naphthothiophenquinone derivatives against epimastigote and trypomastigote forms of T. cruzi and the inhibition of the recombinant enzyme trypanothione reductase (Zani et al 1997).…”
mentioning
confidence: 99%